Participation of National Agrarian University La Molina (Peru) in research on indigenous tenure security leads to changes in forestry curriculum - CGIAR Research Program on Policies, Institutions, and Markets (2018)
PIM partnered with the Forestry Department of the National Agrarian University La Molina in Peru to study land and forest tenure security of indigenous communities using multi-method participatory research. The outcomes of this process include increased knowledge and research capacity of university staff on tenure, gender, and indigenous issues, and changes to the Forest Engineer curriculum to include more social science.